Images of a nation in crisis - Rodwell Makombe (Communicare)
Political cartoonists have, in recent years, faced victimisation for daring to speak truth to power. In December 2010, South African cartoonist, Jonathan Shapiro (Zapiro) was sued for portraying former President Zuma as a rapist. In February 2018, his contract of over ten years with The Sunday Times was abruptly terminated. These developments show that cartoons can be effective tools of undermining and resisting power. This article critically analyses Zapiro’s Rape of Lady Justice cartoons in the context of South African politics under Zuma’s presidency. The ANC-led government under Jacob Zuma was perceived as corrupt and gravitating away from the ideals of a democratic state. Underpinned by Bal et al.’s (2009) model of caricature, this article seeks to examine, firstly, how the cartoon, as a medium of expression, pokes fun at its object of caricature, and secondly, how the broader socio-political context of Zuma’s presidency inspired Zapiro’s Lady Justice cartoons.